Bedouin Questions Addressed to the Prophet - Samadov, Vugar (Scholarya Demo Journal of Ruby, 2021)
The Bedouin tribes constitute the vast majority of the population in the Arabian peninsula. With the arrival of Islam, the peninsula underwent significant changes. These tribes were undoubtedly interested in the developments occurring in the peninsula. Their questions, as well as their confident visit to the Prophet, played a crucial part in the development of Sunnah and hadiths. The Bedouins were accustomed to disorder, rudeness and disobedience as a result of their nomadic lifestyle. Whether deliberately or unintentionally, they used these dispositions against the Messenger of God. We can see how the Prophet worked hard to integrate the Bedouins, who are regarded Arabian Peninsula inhabitants, into the newly formed Islamic community. The Bedouins’ relationship with the Prophet was shaped by their questions. The study of the essence of these issues is particularly useful in illuminating the character and mental world of the Bedouins. The Prophet (pbuh) took a personal interest in the Bedouins who came to Medina, answering their questions, resolving their issues, and sharing their spoils with them. On the whole, the article reveals the Bedouin character by evaluating the questions they asked the Prophet (pbuh) regarding worship, the Day of Judgment, the Hereafter, Paradise, heavenly deeds, jihad, sin and migration.